2011
DOI: 10.3928/1081597x-20110629-01
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Internal Optical Astigmatism on the Correction of Myopic Astigmatism by LASIK

Abstract: Myopic LASIK is less effective in correcting astigmatism when astigmatism is mainly located at the internal optics. Topography and refractive value should be incorporated in the treatment of patients when a significant amount of internal optical astigmatism is detected preoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
26
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(32 citation statements)
references
References 18 publications
4
26
2
Order By: Relevance
“…It makes sense that, given the fact that the magnitude of the ORA seems to be similar in eyes with high myopic astigmatism than in those with low myopic astigmatism, then the ORA/ACA ratio would be higher in the latter group. This fact could explain why the preoperative ORA seems to play a significant role in the refractive outcome of eyes with low preoperative refractive astigmatism, 16,17 but seems to have a negligible effect in eyes with high preoperative astigmatism (as we found in the current paper).…”
Section: Resultssupporting
confidence: 62%
See 3 more Smart Citations
“…It makes sense that, given the fact that the magnitude of the ORA seems to be similar in eyes with high myopic astigmatism than in those with low myopic astigmatism, then the ORA/ACA ratio would be higher in the latter group. This fact could explain why the preoperative ORA seems to play a significant role in the refractive outcome of eyes with low preoperative refractive astigmatism, 16,17 but seems to have a negligible effect in eyes with high preoperative astigmatism (as we found in the current paper).…”
Section: Resultssupporting
confidence: 62%
“…We also found that the visual and refractive results obtained after performing LASIK to correct high myopic astigmatism did not seem to be affected by the magnitude of the preoperative ORA. This seems to contradict the findings of Kugler et al 16 and Qian et al, 17 who studied the effectiveness of LASIK for correcting low myopic astigmatism and found significantly better refractive results in eyes with low ORA than in eyes with high ORA.…”
Section: Resultsmentioning
confidence: 67%
See 2 more Smart Citations
“…If these differences are significant, this may lead to suboptimal visual outcomes. 1,2 The better the correlation between the magnitude and the orientation of the corneal astigmatism and refractive cylinder, the less astigmatism will be left remaining in the optical system of the eye as a whole after treatment.…”
mentioning
confidence: 99%